Exploring Immunomodulatory Approaches in Dentistry: A Comprehensive Review - Amna S. Cheema, Asna Masood, Jia Fatima, Ayesha Tahir, Anna Chaudhary, Dheyaa Al-Alkharsa (South Eastern European Journal of Public Health, 2025)
Immunomodulators alter immune responses and are becoming important therapeutic agents in dentistry that may help treat various oral conditions. They fall into two categories: immunostimulants, which improve immunological function, and immunosuppressants, which lower immune activity. Immunomodulators are essential for regulating inflammation, preventing bone loss, and encouraging tissue regeneration in periodontics. While antibacterial therapy targets harmful bacteria without upsetting the beneficial microbiome, probiotic therapy, on the other hand, aids in restoring microbial equilibrium. Drug therapies, including both pharmacological agents and natural compounds, regulate immune cell function to reduce inflammation and tissue damage. Stem cell-based treatments-especially those using mesenchymal stem cells-help to promote periodontal repair. Gene therapy is a promising approach to modifying immune-related genes to enhance healing and reduce inflammation. These developments demonstrate the important role that immunomodulation plays in treating periodontal disease and provide fresh approaches to enhancing patient outcomes and promoting tissue regeneration.